Pipe ramming (ASCE Manuals and Reports on Engineering Practice ;, 2020)
"MOP 115, Second Edition, describes current pipe ramming practices in design and construction of pipelines under roads, railroads, streets, and other constructed and natural structures and obstacles and includes information on culvert replacements, pipe crushing, slickbores, pipe extraction, as well as assists with horizontal directional drilling projects"--